Changes in Arterial Blood Pressure and Oxygen Tension as a Result of Hoisting in Isoflurane Anesthetized Healthy Adult Horses - Cerullo, Michelle; Driessen, Bernd; Douglas, Hope; Hopster, Klaus (Frontiers in Veterinary Science, 2020)
Background: In anesthetized adult horses, changes in recumbency can influence the cardiovascular system but how arterial blood pressures and oxygen tension change in isoflurane anesthetized animals as a direct result of hoisting has not been investigated. Objective: To evaluate effects of hoisting on hemodynamic function and pulmonary gas exchange in isoflurane-anesthetized horses. Study Design: Prospective, experimental study. Methods: Six adult horses were anesthetized three times using isoflurane in pure oxygen (inspired fraction 0.9–1.0), and allowed breathing spontaneously in lateral recumbency. After 45 min horses were hoisted using a single hoist-hobble system for 5 min and returned into left lateral recumbency. Heart rate (HR), respiratory rate (RR), and systolic (SAP), diastolic (DAP), and mean arterial blood pressures (MAP) were measured every minute starting from 5 min before to 5 min after hoisting. Arterial blood gas samples were collected before, during, and after hoisting. Results: Significant changes in hemodynamic parameters and PaO2 but not PaCO2 were found between baseline recordings and measurements obtained during and early after hoisting. The MAP decreased within the 1st min of hoisting from a mean of 74 ± 17 mmHg at baseline to 57 ± 20 mmHg (p < 0.05). Thereafter, it rapidly recovered to baseline before continuing to rise to higher than baseline values and then remaining elevated for 5 min after horses were returned into lateral recumbency. Simultaneously, the HR increased by 6–9 beats per min during the initial 3 min of hoisting before returning close to baseline values (p < 0.05). The PaO2 decreased significantly from a mean of 324.9 ±137.0 mmHg at baseline to a mean of 141.3 ± 104.2 mmHg during hoisting (p < 0.001) without recovering any more to baseline values. Clinical significance: Hoisting an adult horse during or at the end of isoflurane anesthesia carries the risk of a precipitous, though short-lived (1–2 min), drop in arterial blood pressures and a persistent decrease in arterial oxygenation. While in systemically healthy animals the observed functional impairments were not life-threatening, they may be more severe in systemically compromised horses.Therefore, arterial blood pressures and oxygenation must be carefully monitored when hoisting sick equine patients during or at the end of inhalant anesthesia.